Resepsi Estetik Jauss terhadap Ayat-Ayat Jilbab: Studi Komparatif Sastra Tafsir Kemenag VS. Narasi Hijab Fashion di TikTok - Davin Zachary Yasa; Siti Hanifah Amaliah; Zahira Sufyan; Zahra Mawaddah; Tenny Sudjatnika (Jurnal Teologi Islam, 2026)
The hijab phenomenon in Indonesia has undergone a radical transformation from a static theological signifier to a dynamic visual commodity in the digital era. This research aims to analyze the shift in religious authority and the interpretation of hijab verses (Surah Al-Ahzab: 59 and Surah An-Nur: 31) by comparing the official narrative of the Ministry of Religious Affairs (Kemenag) and the hijab fashion narratives on TikTok. Using Hans Robert Jauss’s Aesthetic of Reception theory, specifically the concepts of "horizon of expectation" and "aesthetic distance," the study employs a comparative analysis on diachronic and synchronic axes. The findings reveal a sharp divergence in reception: Kemenag builds a normative-institutional horizon focusing on legal compliance and moral protection, whereas TikTok constructs an aesthetic-digital horizon driven by algorithmic logic, visibility, and consumerism. This shift demonstrates a radical decentralization of religious authority, where digital influencers act as new interpreters prioritizing "visual orthopraxy" over traditional orthodoxy. Consequently, aesthetics has become a new regime of truth for the younger generation. This study concludes that religious institutions must adopt visual literacy and new interpretive approaches to remain relevant within modern visual culture.